Efficiency of Watermelon rind towards adsorption of Ce (III) and Pr (III) ions. (2022) - Devanathan, R.; Vivekanandan, B.; Rengadurai, S.; Balaji, G.L.; Lakshmipathy, R.
Abstract: The present investigation deals with the utilization of Watermelon rind (WR) as a prolific adsorbent for the removal and recovery of Ce (III) and Pr (III) ions from aqueous solution. The processed WR was used in the batch adsorption studies for optimizing the variables such as pH, contact time, dose and initial metal ion concentration. The maximum loading capacity of the WR was calculated to be 56.8 and 55.3 mg g −1 for Ce (III) and Pr (III) ions respectively. The equilibrium tends to fit well with Langmuir and Freundlich isotherms and pseudo second order kinetic model and further the system is spontaneous and exothermic in nature. The WR has capability of repeated usage which was evidenced from desorption studies. In conclusion, the WR is a potential adsorbent for the sequestration of Ce (III) and Pr (III) ions from aqueous solution.